A Secular Increase in the Equity Risk Premium1 . (7th June 2016) - Daly, Kevin
Abstract: There is an increasing consensus that global 'excess saving' has contributed to a reduction in equilibrium real interest rates. While economists dispute the extent of the decline, few now question that a decline has taken place or that excess saving has played a causal role. A key implication of this narrative is a decline in yields of all assets, including but not restricted to government bond yields. Yet, since the turn of the century, yields on global equity have risen. A complementary explanation is that there has been an increase in the global equity risk premium (ERP), which has simultaneously pushed risk‐free yield curves lower and equity yields higher. Applying a sign restrictions approach, I find that excess savings shocks were the predominant force affecting global real bond yields between the mid‐1980s and 2000 but that 'risk premium' shocks have accounted for more of the decline in real bond yields since 2000.